(3efGQGJ GdSGFQjf Edi Gddg hebGeGJ GdWGFQjf HGddgs - (3CHh HcQ Hf eMeO Hf TGghQ Hf YHO Gddg GdQGRj, fLe GdOjf GdGSOj, OGjI,J (B654 (3g` s ((3GdbGgQI GdeMQhSI s)
(3ChdgG (B:s
(3CeG HYO Cf CUfa cJGHkG cGedkG ai TQM ebGeGJ GdYGQajf TGedkG dcQGeGJ GdSGdcjf s
(3BNQgG (B:s
(3hdG jchf eef QCi Cdag UhGH hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg CLeYjf s
(3GdfSNI HgG MhGTs
(3HgG ebGHdI HBNQgGs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs